Selection of the respiratory phase in minimally invasive interventions for target registration error minimization. (March 2019) - Spinczyk, Dominik; Fabian, Sylwester; Król, Krzysztof
Abstract: Background: In minimally invasive surgery, the main challenge is precisely locating the target during the intervention. For abdominal intervention, one of most important factors causing target motion is breathing. The aim of the study is to efficiently predict target localization during the respiratory in breathing cycle. Method: Analysis of target registration error (TRE) for the registration circuits method was used to find the breathing phase corresponding to the preoperative Computed Tomography spatial configuration. Then, Elastic Body Spline (EBS) for modeling deformation field and Particle Swarm Optimization method were used to find the desired values of EBS parameters: ∝ and stiffness were used. Results: The proposed methodology was verified during experiments conducted on 21 patients diagnosed with liver tumors. This ability of TRE reduction has been achieved for the respiratory phases founded in registration chain analysis. Conclusions: The proposed method presents the usability of spatio-temporal analysis of collected real breathing data in order to estimate the position of a target during the respiratory cycle. This method has been developed to perform operations in real-time on a standard workstation. Highlights: ∙ Reduction of Target Registration Error for minimally invasive intervention was achieved. ∙ Usability of elastic body splines to minimize Target Registration Error was presented. ∙ Particle Swarm optimization approach was used to find parameters of spline curves. ∙ The registration circuits method was used to find the optimal breathing phase for intervention.